Adhesion molecules, endothelin-1 and lung function in seven population-based cohorts. (May 2013) - Oelsner, E. C.; Pottinger, T. D.; Burkart, K. M.; Allison, M.; Buxbaum, S. G.; Hansel, N. N.; Kumar, R.; Larkin, E. K.; Lange, L. A.; Loehr, L. R.; London, S. J.; O'Connor, G. T.; et al.
Abstract Context: Endothelial function is abnormal in chronic obstructive pulmonary disease (COPD); whether endothelial dysfunction causes COPD is unknown. Objective: Test associations of endothelial biomarkers with FEV1 using instrumental variables. Methods: Among 26 907 participants with spirometry, ICAM-1, P-selectin, E-selectin and endothelin-1 were measured in subsets. Results: ICAM-1 and P-selectin were inversely associated with FEV1 among European-Americans (−29 mL and −34 mL per standard deviation of log-transformed biomarker, p < 0.001), as was endothelin-1 among African-Americans (−22 mL, p = 0.008). Genetically-estimated ICAM-1 and P-selectin were not significantly associated with FEV1. The instrumental variable for endothelin-1 was non-informative. Conclusion: Although ICAM-1, P-selectin and endothelin-1 were inversely associated with FEV1, associations for ICAM-1 and P-selectin do not appear causal.